Orphan Legumes Growing in Dry Environments: Marama Bean as a Case Study - Cullis, Christopher; Chimwamurombe, Percy; Barker, Nigel; Kunert, Karl; Vorster, Juan (Frontiers in Plant Science, 2018)
Plants have developed morphological, physiological, biochemical, cellular and molecular mechanisms to survive in drought-stricken environments with little or no water caused by below-average precipitation. In this mini-review, we highlight the characteristics that allows marama bean [Tylosema esculentum (Burchell) Schreiber], an example of an orphan legume native to arid regions of southwestern Southern Africa, to flourish under an inhospitable climate and dry soil conditions where no other agricultural crop competes in this agro-ecological zone. Orphan legumes are often better suited to withstand such harsh growth environments due to development of survival strategies using a combination of different traits and responses. Recent findings on questions on marama bean speciation, hybridization, population dynamics, and the evolutionary history of the bean and mechanisms by which the bean is able to extract and conserve water and nutrients from its environment as well as aspects of morphological and physiological adaptation will be reviewed. The importance of the soil microbiome and the genetic diversity in this species, and their interplay, as a reservoir for improvement will also be considered. In particular, the application of the newly established marama bean genome sequence will facilitate both the identification of important genes involved in the interaction with the soil microbiome and the identification of the diversity within the wild germplasm for genes involved drought tolerance. Since predicted future changes in climatic conditions, with less water availability for plant growth, will severely affect agricultural productivity, an understanding of the mechanisms of unique adaptations in marama bean to such conditions may also provide insights as to how to improve the performance of the major crops.